The wrong murder : a Jake Justus mystery - Rice, Craig, 1908-1957; Hoffman, H. Lawrence; Popular Library (New York, N.Y.) (New York : Popular Library, 1940)
Socialite Mona McClane bets Jake Justis, on his wedding day, that she can commit the perfect murder. The next day there is a newspaper report detailing the murder of a man taking place on one of Chicago’s busiest streets. Wife Helene and lawyer John J. Malone help investigate.
"A Popular library wartime book"--T.p. verso.
Reginald, R. Cumulative paperback index, 1939-1959
Schreuders, P. Paperbacks, U.S.A.
Reginald, R. Cumulative paperback index, 1939-1959
Mode of access: Internet.
Keywords: Malone, John J. -- (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Chicago (Ill.) -- Fiction; Detective and mystery fiction; Mystery fiction; Fiction; Detective and mystery fiction; pulp fiction; Pulp literature, American